“A study on how UiTM bachelor students manage stress”: a study of UiTM Sarawak/ Vyviana Julan Lihan… [et.al]. - Lihan, Vyviana Julan; Md Saad, Hashimi; Sazali, Saliana; Ghafar, Bibu (Universiti Teknologi MARA, Sarawak, 2005)
A study on how UiTMCS Bachelor student manage stress is in order to know their own recommendations and suggestions towards it. Furthermore is where we want to know and to identify what are their perception about stress, the sources and effects of stress, and their strategies on how to reduce their stress. And within the study, we also hope that it can help most of the students on how to reduce and overcome their stress.